The Effect of Attribute Alignability on Product Purchase: The Moderating Role of Product Familiarity and Self-Construal - Zhang, Yong; Wen, Yuwen; Hou, Min (Frontiers in Psychology, 2021)
Previous studies on Structural Alignment Model suggest that people compare the alignable attributes and nonalignable attributes during the decision making and preference formation process. Alignable attributes are easier to process and more effective in clue extracting, so it is believed that people rely more on alignable than nonalignable attributes when comparing alternatives. While this article supposes that consumers’ product experience and personal characteristics also play a significant role in regulating consumers’ reliance on attribute alignability. The authors conducted three experiments to examine the moderating role of consumers’ product familiarity and self-construal in the impact of attribute alignability on consumer product purchase. The results show that: (1) When making a purchase decision, consumers with a high level of product familiarity will rely more on nonalignable attributes, while those with a low level of product familiarity will rely more on alignable attributes. (2) The difference in consumer dependency on attribute alignability is driven by their perceived diagnosticity of attributes. (3) The dependency of consumers with different levels of familiarity on attribute alignability will be further influenced by consumers' personal characteristics, self-construal. Individuals with interdependent self-construal rely more on alignable attributes when unfamiliar with the product and rely more on nonalignable attributes when familiar with the product. Individuals with independent self-construal, however, rely more on nonalignable attributes regardless of the degree of product familiarity. The conclusions of this paper can be used as references for enterprises to establish product positioning and communication strategies.